The Role of Lymphoid Neogenesis in Allografts - Hsao, Hsi-Min (Am J Transplant, 2016)
De novo induction of organized lymphoid aggregates at non-lymphoid sites has been observed in many chronic inflammatory conditions where foreign antigens such as infectious agents, auto- or alloantigens, persist. The prevailing opinion in the field of transplantation is that lymphoid neogenesis within allografts is detrimental to the establishment of immune tolerance. These structures, commonly referred to as tertiary lymphoid organs (TLOs), are thought to contribute to graft rejection by generating and propagating local alloimmune responses. However, recent studies have shown that TLOs rich in regulatory Foxp3(+) cells are present in long term accepting allografts. The notion that TLOs can contribute to the local downregulation of immune responses has been corroborated in other chronic inflammation models. These findings suggest that contrary to previous suggestions that the induction of TLOs in allografts is necessarily harmful, the induction of “tolerogenic” TLOs may prove advantageous. In this review, we discuss our current understanding of how TLOs are induced and how they regulate immune responses with a particular focus on alloimmunity.